2005
DOI: 10.1590/s1413-65382005000200002
|View full text |Cite
|
Sign up to set email alerts
|

Inclusão de crianças em educação pré-escolar regular utilizando comunicação suplementar e alternativa

Abstract: Muitas crianças usuárias de meios alternativos de comunicação se encontram educacionalmente segregadas, mesmo não havendo evidências de que tais ambientes pudessem ser mais benéficos na promoção de sua comunicação e do desenvolvimento da linguagem do que ambientes não segregados. Os efeitos potencialmente positivos do ambiente escolar inclusivo ainda não foram plenamente descritos. No entanto, explicações teóricas recentes sobre o desenvolvimento lingüístico sugerem que a comunicação e o desenvolvimento de lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
28

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 39 publications
0
5
0
28
Order By: Relevance
“…Children with lack of speech, but users of alternative communication systems are able to understand and make themselves understood in the world of language. It can be achieved through looks, gestures, facial expressions and body posture, allowing their interaction with others and a greater insertion in society [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Children with lack of speech, but users of alternative communication systems are able to understand and make themselves understood in the world of language. It can be achieved through looks, gestures, facial expressions and body posture, allowing their interaction with others and a greater insertion in society [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic of true inclusion is that it comprises not only direct educational situations but the whole set of events and activities that are the foundation of meaning making in kindergarten and school, including play and social interaction during breaks and on the way to and from kindergarten and school (MULVIHILL; SHEARER; VAN HORN, 2002;VON TETZCHNER et al, 2005). Inclusion is thus not only about developing academic skills or increasing wanted and reducing unwanted behavior, but about enculturation in a broad sense.…”
Section: Santa Mariamentioning
confidence: 99%
“…Many developmental researchers have pointed out that horizontal peer relations afford interactions that are qualitatively different from those of the vertical adult child relations (PIAGET, 1932;DUNN, 1988DUNN, , 1999KEMPLE, 2004;HARTRUP, 1989). Studies have found that the interaction with peers may facilitate learning and development in children with ASD and other disabilities (GULDBERG, 2010;VON TETZCHNER et al, 2005). Interaction with peers may contribute to inclusion and the development of social and cultural knowledge and skills in a way that cannot be easily achieved by teacher instruction and adult child interactions.…”
Section: Santa Mariamentioning
confidence: 99%
See 1 more Smart Citation
“…Nessa direção, grupos de pesquisadores consideram a CSA como um recurso linguístico que pode mediar relações estabelecidas por sujeitos com graves comprometimentos da oralidade, contribuindo de forma decisiva em seus processos de inclusão social (HUER; PARETTE; SAENZ, 2001;PANHAN, 2001;CHUN, 2003;VASCONCELLOS, 2009). Ressalta-se o papel fundamental que a incorporação de modos de linguagem de natureza corporal e gráfi ca podem trazer para a construção da autonomia de tais sujeitos (LACERDA, 2000;VON TETZCHNER, 2005;REILY, 2006).…”
Section: Introductionunclassified